High‐Throughput Atomic Layer Deposition of P‐Type SnO Thin Film Transistors Using Tin(II)bis(tert‐amyloxide). Issue 9 (3rd February 2022) - Mameli, Alfredo; Parish, James D.; Dogan, Tamer; Gelinck, Gerwin; Snook, Michael W.; Straiton, Andrew J.; Johnson, Andrew L.; Kronemeijer, Auke J.
Abstract: Spatial atomic layer deposition (sALD) of p‐type SnO is demonstrated using a novel liquid ALD precursor, tin(II)‐bis(tert‐amyloxide), Sn(TAA)2, and H2 O as the coreactant in a process which shows an increased deposition rate when compared to conventional temporal ALD. Compared to previously reported temporal ALD chemistries for the deposition of SnO, deposition rates of up to 19.5 times higher are obtained using Sn(TAA)2 as a precursor in combination with atmospheric pressure sALD. Growths per cycle of 0.55 and 0.09 Å are measured at deposition temperatures of 100 and 210 °C, respectively. Common‐gate thin film transistors (TFTs), fabricated using sALD with Sn(TAA)2 result in linear mobilities of up to 0.4 cm 2 V –1 s –1 and on / off‐current ratios, I On / I Off > 10 2 . The combination of enhanced precursor chemistry and improved deposition hardware enables unprecedently high deposition rate ALD of p‐type SnO, representing a significant step toward high‐throughput p‐type TFT fabrication on large area and flexible substrates. Abstract : A novel precursor for SnO atomic layer deposition (ALD) is employed for the first time in spatial‐ALD. The synergy between precursor chemistry and deposition hardware affords deposition rates up to 19.5 times faster than with established SnO precursors. Good p‐type electrical performance, linear mobilities up to 0.4 cm 2 V –1 s –1 are demonstrated with common gate thin film transistors.